2007
DOI: 10.1016/j.virol.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Transcription releases protein VII from adenovirus chromatin

Abstract: Adenovirus protein VII is the major protein component of the viral nucleoprotein core. It is a nonspecific DNA-binding protein that condenses viral DNA inside the capsid. Protein VII remains associated with viral chromatin throughout early phase, indicating its continuing role during infection. Here we characterize the release of protein VII from infectious genomes during a time period that corresponds to the late phase of infection. Interestingly, the early viral transactivator E1A, but not other early gene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 49 publications
6
77
0
Order By: Relevance
“…During herpesvirus lytic infection, the viral genomes are associated with histones immediately after injection into the nucleus, and viral proteins are required to enhance histone acetylation to allow for efficient viral gene expression (40)(41)(42)(43)(44). Moreover, studies of infection by an adenovirus have shown that viral proteins mediate the transcriptional activation of viral promoter regions (45)(46)(47). In this work, we first observed that the progress of CPV infection was accompanied by the enrichment of H3 histones in the enlarged APAR body area.…”
Section: Discussionmentioning
confidence: 78%
“…During herpesvirus lytic infection, the viral genomes are associated with histones immediately after injection into the nucleus, and viral proteins are required to enhance histone acetylation to allow for efficient viral gene expression (40)(41)(42)(43)(44). Moreover, studies of infection by an adenovirus have shown that viral proteins mediate the transcriptional activation of viral promoter regions (45)(46)(47). In this work, we first observed that the progress of CPV infection was accompanied by the enrichment of H3 histones in the enlarged APAR body area.…”
Section: Discussionmentioning
confidence: 78%
“…Data from immunofluorescence-based experiments suggested that core VII remains stably associated with wild-type Ad DNA throughout the early phase of infection, until the onset of late gene expression (ϳ10 to 12 hpi), and that transcription is necessary to evict core VII (10). Using hdAd which contained only noncoding DNA (i.e., lacked a transgene), VII was shown to remain stably associated with the vector DNA until at least 18 hpi by immunofluorescence analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, even up to 24 hpi, a small proportion of VII does persist in the nucleus and may be associated with the vector DNA. Previous work by Chen and coworkers demonstrated that the level of VII within cells changed very little between 4 and 12 hpi and that foci of VII (presumably VII-associated viral genomes) could be detected in the nucleus by immunofluorescence for up to ϳ12 hpi (10). However, that report did not examine the levels of VII at earlier time points (i.e., between 0 and 4 hpi) or whether the nuclear foci of VII contained Ad DNA completely or only partially wrapped in VII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial work on the adenovirus genome showed transcriptiondependent chromatinization of the adenoviral genome (29). Since this discovery, the importance of the chromatinization of the viral genome in DNA damage (30) and transcription control (31,32) has become increasingly apparent.…”
Section: Discussionmentioning
confidence: 99%